The living dead: acknowledging life after tree death to stop forest degradation. Issue 9 (3rd September 2020) - Thorn, Simon; Seibold, Sebastian; Leverkus, Alexandro B; Michler, Thomas; Müller, Jörg; Noss, Reed F; Stork, Nigel; Vogel, Sebastian; Lindenmayer, David B
Abstract : Global sustainability agendas focus primarily on halting deforestation, yet the biodiversity crisis resulting from the degradation of remaining forests is going largely unnoticed. Forest degradation occurs through the loss of key ecological structures, such as dying trees and deadwood, even in the absence of deforestation. One of the main drivers of forest degradation is limited awareness by policy makers and the public on the importance of these structures for supporting forest biodiversity and ecosystem function. Here, we outline management strategies to protect forest health and biodiversity by maintaining and promoting deadwood, and propose environmental education initiatives to improve the general awareness of the importance of deadwood. Finally, we call for major reforms to forest management to maintain and restore deadwood; large, old trees; and other key ecological structures.